2021
DOI: 10.1007/s13311-021-01166-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Neurography: Improved Diagnosis of Peripheral Neuropathies

Abstract: Peripheral neuropathies account for the most frequent disorders seen by neurologists, and causes are manifold. The traditional diagnostic gold-standard consists of clinical neurologic examinations supplemented by nerve conduction studies. Due to well-known limitations of standard diagnostics and atypical clinical presentations, establishing the correct diagnosis can be challenging but is critical for appropriate therapies. Magnetic resonance neurography (MRN) is a relatively novel technique that was developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 125 publications
1
19
1
3
Order By: Relevance
“…Tibial fascicles of the left sciatic nerve and their distal continuation as tibial nerve with coverage from the proximal thigh down to the distal ankle were segmented on 140 axial slices/ participant generated by sequence (2) by one neuroradiologist (J.K.) blinded to clinical data. To exclude significant side differences, the tibial nerve was additionally segmented on 35 axial slices at the right mid to distal thigh, a region where previous studies predominantly identified nerve lesions in different neuropathies [7,[14][15][16].…”
Section: Image Post-processing and Analysesmentioning
confidence: 99%
“…Tibial fascicles of the left sciatic nerve and their distal continuation as tibial nerve with coverage from the proximal thigh down to the distal ankle were segmented on 140 axial slices/ participant generated by sequence (2) by one neuroradiologist (J.K.) blinded to clinical data. To exclude significant side differences, the tibial nerve was additionally segmented on 35 axial slices at the right mid to distal thigh, a region where previous studies predominantly identified nerve lesions in different neuropathies [7,[14][15][16].…”
Section: Image Post-processing and Analysesmentioning
confidence: 99%
“…MRN technology can evaluate peripheral nerves with a diameter of 2 mm and above and identify the fine structure of peripheral nerves [ 7 ]. Among the sequences, DTI is a noninvasive functional MR technology developed on the basis of diffusion-weighted imaging to display the fine structure of tissues [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance neuroimaging (MRN) can obtain high-resolution 3-dimensional images of nerve fibers, which can provide a basis for the diagnosis of peripheral neuropathy [ 7 ]. Traditional neuro-electromyography has poor diagnosis efficiency of nerve lesions and is highly subjective.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the MRN method provides an excellent and accurate 3D anatomy of the peripheral nerves. However, MRN is challenging due to various factors such as insufficient suppression of vascular signals, spatial resolution, subject motion, insufficient fat-signal suppression and surrounding structures involved in the quality of the acquired data ( 44 , 45 ). With respect to this, the conventional 3D-T2-STIR MRN cannot visualize the neighboring vessels and therefore it cannot assess their involvement in brachial plexopathy.…”
Section: Discussionmentioning
confidence: 99%